La metrópolis en la historia: apuntes para la comprensión del hábitat metropolitano contemporáneo (2019)
The urban growth and metropolitan development have changed the way to live for the contemporary human being; nevertheless this process is not accidenta: diverse historical moments of metropolis allows to understand what metropolitan habitat means and which are the attributes that step by step it has gain until the actual moment, especially in Latin America